Laser Based Vibration Sensor Through Mobile - Rashmita K. Mohapatra; Shalini J. Yadav; Rajan Yadav (Universitas Sanata Dharma, 2023)
Machine condition monitoring has gained momentum over the years and becoming an essential component in the today’s industrial units. A cost-effective machine condition monitoring system is need of the hour for predictive maintenance. The paper presents the design and implementation using vibration sensor, and also this system operated through smart phones. Vibration analysis plays a major role in detecting machine defects and developing flaws before the equipment fails and potentially damages. The concept of this project was to detect faulty equipment in industry machine so that before damaging the whole machine faulty equipment can be replace and improve the durability of machine.